The Impact of Customer Satisfaction on Loyalty of GoTo: The Application of Technology Adoption Model (TAM) - Putri, Marsha Rachmanda; Aprianingsih, Atik (School of Business, IPB University (SB-IPB), 2024)
The rise of digitalization has shifted consumers to do activities online including purchasing or ordering transportation online. The habit of relying on the internet and using applications to do transactions gives massive benefits to e-commerce and ride-hailing companies to the extent they become unicorn business level for startups. Taken from Indonesia's case, Gojek and Tokopedia is a product of e-commerce in the field of multi-service technology and digital payment. Within the merged, this study is to investigate the Technology adoption model (TAM) with the two fundamental variables of perceived ease of use (EOU) and perceived usefulness (PU). Enhancing the examination, perceived privacy security (PPS) is tested along with TAM to examine customer satisfaction. This research was empirically analyzed with SEM-PLS as its statistical analysis. This research was conducted in Indonesia, in the mid of the year of 2022. Questionnaires are distributed as the survey, by having GoTo users as the population. Our findings show that perceived ease of use and perceived usefulness are positively significant on consumer satisfaction. Contrary to the findings in previous research, in the Indonesian context, perceived privacy security has less impact on consumer satisfaction. This research objective is to generate more sustainable e-commerce users through the use of digital loyalty programs. Insights for the managerial in e-commerce marketing are discussed. Keywords: consumer satisfaction, loyalty program, technology acceptance model, e-commerce